An Assessment of Levels of Iodine in Iodised Salt Retailed in the Ghanaian Markets - Bartels, Benjamin; Victor Patrick Yao Gadzekpo (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
The salt iodization law of Ghana prescribed that edible salt meant for animal and human consumption must be iodised with potassium iodate. The level is set between 25-50ppm by the Ghana Standard Authority for retail and production respectively. Packaged (refined) and unpackaged (crude) salts samples randomly obtained from selected locations across the then ten (10) regions of Ghana in fourteen (14) months, were analysed for their iodine content using classical titrimetric method. For the refined, 465 samples made up of 2 types, imported (7) and local (3), whilst the crude were 126 samples. None of the samples was compliant with the 25µg/g iodine level prescribed in the law for retail. For instance, sample F refined, with a relatively wider distribution in this study, had a mean iodine content of 50.1± 0.02µg/g, whilst crude sample from Upper West region being the only iodised salt recorded an average of 51.6 ± 0.002 µg/g iodine at the retail. Questionnaire responses revealed that the choice of salt type depends on availability, affordability, and not necessarily, iodine content. The responses also showed ignorance about the manner of use of the type of salt.